2016
DOI: 10.3390/healthcare4030059
|View full text |Cite
|
Sign up to set email alerts
|

Biopsychosocial Characteristics, Using a New Functional Measure of Balance, of an Elderly Population with CLBP

Abstract: This study examined the biopsychosocial characteristics of chronic low back pain (CLBP) in an understudied but increasingly larger part of the population: the elderly (i.e., 65 years and older). A new innovative physical functioning measure (postural control, which is a proxy for the common problem of slips and falls in the elderly) was part of this biopsychosocial evaluation. Also, the National Institutes of Health (NIH)-developed Patient-Reported Outcome Measurement Information System (PROMIS) was also part … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Previous data that indicate the influence of health status on LBP disability are consistent with this result 9,46 . However, it is essential to note that the available literature on LBP in the general population has shown meaningful participation of psychological and social issues in detriment of clinical and biological issues [18][19][20]37,44 . This is also evident in this study since several biological factors did not show a significant association with disability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous data that indicate the influence of health status on LBP disability are consistent with this result 9,46 . However, it is essential to note that the available literature on LBP in the general population has shown meaningful participation of psychological and social issues in detriment of clinical and biological issues [18][19][20]37,44 . This is also evident in this study since several biological factors did not show a significant association with disability.…”
Section: Discussionmentioning
confidence: 99%
“…The scientific literature highlights the importance of the biopsychosocial model in the approach of LBP in the general population [17][18][19][20] . However, on the association of biopsychosocial factors with disability in LBP patients are still limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al reported that CLBP patients performed significantly worst in every aspect of postural control compared to older patients not suffering from chronic pain [52] . Similarly, a study conducted by Hulla et al examined biopsychosocial measures in older adults affected by CLBP compared to match (age, gender, education, and exercise engagement) non-CLBP counterparts [53] . The study revealed that older adults with CLBP associated with worse scores on conditions related to postural control and fall risk; and CLBP individuals suffered from greater pain intensity, fatigue, sleep disturbance, and lower levels of perceived physical function than their non-CLBP matched counterparts.…”
Section: Chronic Pain Effect On Postural Control and Gaitmentioning
confidence: 99%
“…Risk factors, such as anxiety, cognitive deficiencies, depression, declining vision, decreased physical activity, weakening neuromuscular factors, osteoarthritis, and increased psychotropic medication and diuretic consumption, can all contribute to sustaining a fall-related injury [8][9][10]. A study conducted by Hulla et al provided an example of new important issues of chronic pain and "fall-risk, " by revealing that older adults with CLBP performed more poorly in balance-activities and various psychosocial dimensions, relative to their demographically-matched counterparts without CLBP [11]. Relatedly, in regards to exercise in aiding in the management of chronic pain in the older-adult population, a study by Stubbs et al demonstrated that adequate exercise can have an influence in reducing falls in older adults by enhancing psychosocial and physical functioning [12].…”
mentioning
confidence: 99%